Severe respiratory acidosis contributing to refractory hyperkalemia: a case series of COVID-19 patients with renal failure - Nabadwip Pathak; Sunil Kumar Nanda (Journal of Nephropharmacology)
Introduction: Respiratory acidosis (RA) is not known to cause severe hyperkalemia. However, an exception to this general rule was observed in three patients with severe COVID-19 complicated with renal failure in our center. Objectives: The current study investigated the explanation for hyperkalemia refractory to renal replacement therapy in patients with severe COVID-19 with hypercarbia and renal failure in a tertiary care center. Patients and Methods: In this study, we present a case series of three patients with severe COVID-19 with hypercarbia and dialysis-requiring renal failure who developed persistent hyperkalemia refractory to renal replacement therapy. We studied various causes of persistent hyperkalemia, such as acid‒base disorder, a high turnover state, exogenous administration, rhabdomyolysis, and hypoaldosteronism. Results: All three patients initially presented with episodes of severe hyperkalemia, which were ameliorated after RA was corrected. All of these patients had worsening pulmonary function, after which the hyperkalemia could not be corrected, corresponding to persistent RA. The evidence that there was a contribution of RA to hyperkalemia was further strengthened by the observations of patient 1, in whom the hyperkalemia was only corrected after changing ventilator settings and who was unresponsive to dialysis. We studied the dialysate effluent in patient 3, and the results showed satisfactory removal of potassium with no improvement in the high serum potassium levels. Another interesting finding was that although the dialysate sodium concentration was greater than the serum sodium concentration, there was a decrease in the serum sodium concentration, indicating a reduced movement of sodium into the extracellular space. Conclusion: In our study, metabolic acidosis alone could not explain the high serum potassium levels. Moreover, hyperkalemia was corrected after RA was corrected, indicating that the latter might have been the predominant cause of hyperkalemia in these scenarios. The presence of renal failure and low serum bicarbonate levels might have been the factors contributing to decreased Na+-K+-ATPase activity in the setting of RA, which contributed to severe hyperkalemia in all three patients.